THE IMPACT OF VIDEO GAMES TOWARD STUDENTS’ SPEAKING ABILITY - Muhammad, Agung; Herman, Yuli; Permata, Riyen (Universitas Mahaputra Muhammad Yamin, 2025)
In Indonesia, many students still face challenges in developing their English-speaking skills due to limited practice opportunities and a strong focus on written exams. However, some students have shown strong speaking abilities without attending extra English lessons. This study explores the possible link between video game playing and speaking skill improvement in such cases. While informal language learning through digital media has been recognized, the specific impact of video gaming on speaking abilities—especially in the Indonesian junior high school context—remains underexplored. This descriptive qualitative study involved 30 eighth-grade students at SMP Negeri 2 Kota Solok in the 2023/2024 academic year who regularly played video games and demonstrated above-average speaking skills based on school performance and teacher evaluation. Data were collected through interviews, classroom observation, and students’ report card analysis, then analyzed using thematic analysis to identify common patterns and insights. The results show that online multiplayer games such as Mobile Legends, Free Fire, and Roblox helped students improve fluency, pronunciation, and vocabulary through frequent English communication with other players. These findings suggest that video games can be a valuable source of speaking practice, and they highlight the potential for educators and policymakers to consider integrating digital media as a complementary tool in language learning.